2019
DOI: 10.1002/qj.3555
|View full text |Cite
|
Sign up to set email alerts
|

Urban impacts on the spatiotemporal pattern of short‐duration convective precipitation in a coastal city adjacent to a mountain range

Abstract: The present study examines urban impacts on short‐duration precipitation in an idealized coastal city adjacent to a mountain range using two‐dimensional idealized simulations performed with a modified version of the Weather Research and Forecasting (WRF) model. A unique aspect of this study is that an ensemble simulation approach with 243 members is used with sensitivity experiments to reduce uncertainty arising from nonlinearity in the precipitation simulation and to evaluate the statistical significance. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Other studies over coastal cities have found enhanced convection associated with the convergence of SB and UHI circulations over and downwind of urban areas (Yoshikado, 1992; Kitada et al ., 1998; Freitas et al ., 2007; Kusaka et al ., 2019). This effect is not apparent here, as the urban circulation in the north of SGJB is masked by the complex flow between individual thunderstorm cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies over coastal cities have found enhanced convection associated with the convergence of SB and UHI circulations over and downwind of urban areas (Yoshikado, 1992; Kitada et al ., 1998; Freitas et al ., 2007; Kusaka et al ., 2019). This effect is not apparent here, as the urban circulation in the north of SGJB is masked by the complex flow between individual thunderstorm cells.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction with the UHI circulation alone has been found to trigger, reinforce and modify the timing and location of convection in Houston, USA (Shepherd and Burian, 2003; Shepherd et al ., 2010), Nohbi Plain, Japan (Kitada et al ., 1998), Chennai, India (Simpson et al ., 2008), and Taipei, Taiwan (Lin et al ., 2011). More recently, enhancement of onshore SB moisture transport, together with increased instability due to higher urban surface sensible heat flux, has been found to result in increased precipitation in Tokyo, Japan (Kusaka et al ., 2014; 2019), Jakarta, Indonesia (Argüeso et al ., 2016), Kuala Lumpur, Malaysia (Argüeso et al ., 2016; Ooi et al ., 2017; Li et al ., 2020) and Singapore (Doan et al ., 2021, hereafter D21).…”
Section: Introductionmentioning
confidence: 99%
“…For cities located in geographically or topographically complex locations, urban effects interact with other mesoscale circulations such as the land–sea or mountain–valley breezes, which complicate the processes generating precipitation (e.g. Gero and Pitman, 2006; Lin et al ., 2011; Kusaka et al ., 2014; 2019; Argüeso et al ., 2016; Freitag et al ., 2018). For example, a stronger sea breeze (as a secondary urban effect) could transport more moisture onshore, thus enhancing the chance of convection and precipitation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over Beijing, Dou et al (2015) found, however, that depending on the strength of the UHI, maximum precipitation values were found either over the most urbanized area of Beijing in the case of strong UHI (> 1.25 °C) or along its downwind lateral edges for a weak UHI (< 1.25 °C). Theoretical analysis (Han and Baik 2008) and regional climate models using urban canopy parameterizations (Trusilova et al 2008;Kusaka et al, 2014Kusaka et al, , 2019Pathirana et al 2014;Ganeshan and Murtugudde 2015;Zhong and Yang 2015;Song et al 2016;Zhong et al 2017;Zhu et al 2017;Li et al 2017;Ooi et al 2017) have been used to simulate the impact of urbanization on the precipitation patterns near urban centers. Three mechanisms could be assessed: (1) upward motion induced by the urban heat island circulation can initiate moist convection by Published in partnership with CECCR at King Abdulaziz University creating an urban-induced convergence which may interact with sea breeze for coastal cities, (2) increased urban roughness which may attract propagating storms toward the urban centers, and (3) urban aerosols which may interact synergistically with the previous mechanisms producing a rainfall enhancement (Schmid and Niyogi 2014).…”
Section: Urban Climate and Regional Scale Changementioning
confidence: 99%
“…Similar effect was found in the Suzhou-Wuxi area (China) by Zhang and Chen (2014) and more recently over the UK by Bassett et al (2017) where the heat advection from small urban centers increases the mean nocturnal air temperature by 0.6 °C up to a horizontal distance of 0.5 km. There are also examples of interaction between sea-breeze front penetration and urban areas, either enhancing the sea-breeze front (Kusaka et al 2000(Kusaka et al , 2019Li et al 2015) or decelerating its penetration inland (Yoshikado and Kondo 1989;Kusaka et al 2000Kusaka et al , 2019Hamdi et al 2012a;Rojas et al 2018) and therefore impacting the spatial distribution of the urban heat island. Finally, there is also evidences of synergistic interactions between UHI and heat wave episodes making the heat wave more intense in urban than rural areas and the nocturnal UHI during heat wave stronger than its climatological mean: along the Washington-Baltimore corridor in the US (Li and Bou-Zeid 2013), across the Yangtze River Delta in China (Wang et al 2017), Western Europe, Brussels (Hamdi et al 2016), and in the Mediterranean climate, Athens (Founda and Santamouris 2017).…”
Section: Urban Climate and Regional Scale Changementioning
confidence: 99%